2007
DOI: 10.1523/jneurosci.5279-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity in the Primary Somatosensory Thalamocortical Loop Is Modulated by Reward Contingency during Tactile Discrimination

Abstract: Delayed-response sensory discrimination is believed to require primary sensory thalamus and cortex for early stimulus identification and higher-order forebrain regions for the late association of stimuli with rewarded motor responses. Here we investigate neuronal responses in the rat primary somatosensory cortex (S1) and ventral posterior medial nucleus of the thalamus (VPM) during a tactile discrimination task that requires animals to associate two different tactile stimuli with two corresponding choices of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 45 publications
3
49
0
2
Order By: Relevance
“…For this, we used a classifier and tested the amount of information above chance level that was present in sessions with neural activity recorded from supragranular, granular, or infragranular layers. As previously reported (Krupa et al 2004;Pantoja et al 2007;Wiest et al 2010), neural activity in all different layers contained sufficient information to decode the aperture width significantly above chance (see Fig. 15, open bars).…”
Section: S1 Neurons Reflect Vpm or Pom Dynamicssupporting
confidence: 83%
See 2 more Smart Citations
“…For this, we used a classifier and tested the amount of information above chance level that was present in sessions with neural activity recorded from supragranular, granular, or infragranular layers. As previously reported (Krupa et al 2004;Pantoja et al 2007;Wiest et al 2010), neural activity in all different layers contained sufficient information to decode the aperture width significantly above chance (see Fig. 15, open bars).…”
Section: S1 Neurons Reflect Vpm or Pom Dynamicssupporting
confidence: 83%
“…Indeed, the behavior of supragranular, granular, and infragranular layer neurons varied according to the distinct epochs that defined a tactile discrimination task trial. In previous studies, we have shown that, during the anticipatory period, the firing modulations of S1 infragranular layer neurons were fundamentally different from the ones observed in layers II/III and IV (Krupa et al 2004;Pais-Vieira et al 2013b;Pantoja et al 2007;Wiest et al 2010). We have also shown that M1 was partially responsible for these specific infragranular neuron-firing patterns (Pais-Vieira et al 2013b).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Demonstrations of reward dependent sustained activity in somatosensory cortex (11) and sustained responses in auditory cortex (8) might indicate that temporal and reward processing occur in lower order areas of the brain than previously thought. Additionally, because local neural populations throughout the cortex meet our model's minimal requirements, the fundamental concept of using an external signal to modulate plasticity (23,24) could be the basis of elementary mechanisms used throughout the brain to process time.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on the role of learned value in biasing the neural mechanisms that are involved in planning and executing eye movements, suggesting an influence of value on decision making at a relatively late stage of information processing (Dorris and Glimcher 2004;Platt and Glimcher 1999;Seo and Lee 2008;Seo et al 2009;Sugrue et al 2004Sugrue et al , 2005. However, several recent studies have shown that value also modulates neural gain in early sensory areas that are thought to encode low-level stimulus features, such as primary visual and somatosensory cortex (V1 and S1, respectively; Pantoja et al 2007;Pleger et al 2008Pleger et al , 2009Serences 2008;Shuler and Bear 2006). These later results imply that value biases decision making not only by differentially weighting motor responses, but also by biasing the quality of relevant sensory inputs (but see Liston and Stone 2008).…”
Section: Introductionmentioning
confidence: 99%